TUBERIZATION IN HEAT TOLERANT HYBRID HT/92-621 UNDER CONTROLLED TEMPERATURE CONDITIONS - Minhas, J. S.; Kumar, Devendra (Potato Journal, 2013)
Hybrid HT/92-621, suitable for cultivation in peninsular and coastal parts of India as well as for early planting in north-western plains, has recently been recommended for release as the first heat tolerant variety of CPRI. Although the hybrid is able to tuberize under high night temperature conditions, yet this character has not been quantified in detail. Therefore, tuberization in leaf bud cuttings of this hybrid was studied along with Kufri Chandramukhi (control) at 24 and 27°C day temperature in combination with 18, 20, 22 and 24°C night temperatures. HT/92-621 was able to tuberize at all the night temperatures but good tuberization was observed up to 22°C night temperature, whereas, cv. Kufri Chandramukhi gave good tuberization at 18°C. The tuber fresh weight was higher at 24°C than 27°C day temperature in both the varieties.